FROM THE ARAL TO ROGUN: THE WATER SITUATION IN THE AMU DARYA BASIN TODAY - RAKHIMOV, Sulton; KAMOLIDINOV, Anvar (CENTRAL ASIA AND THE CAUCASUS, 2014)
Recently, the problems related to water usage in the Central Asia Region have not left the pages of the media and Internet websites. Particular attention is being focused on the most urgent topic— building hydropower stations on the upper reaches of the Amu Darya and Syr Darya rivers, which are the region’s main water arteries.This article presents an analysis of the water situation in the Amu Darya Basin, including the reasons for the shrinkage of the Aral Sea. It draws a picture of how water resources form, are distributed, and used in the Amu Darya Basin, and gives probable forecasts of the potential positive and negative consequences of building the Rogun Hydropower Plant, keeping in mind the influence of the current global challenges and threats for the region. It draws attention to the weak regional cooperation and the possible development of negative trends caused by limited integration. The difficulties associated with stable water supply to the region’s countries can only be avoided by establishing cooperation among them.